2021
DOI: 10.3390/info12110449
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Determine the Adoption Intention of Direct Mobile Purchases through Social Media Apps

Abstract: In the last few years, a number of social media e-business models including the social networking giants of Facebook, Pinterest and Instagram have offered direct purchase abilities to both their users and the involved enterprises. Hence, individuals can buy directly without having to leave the social media website. At the same time, there is a significant increase in the number of online purchases through mobile devices. To add to this, nowadays, the vast majority of internet users prefer to surf via their sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
1
4
0
1
Order By: Relevance
“…Following Corbitt et al's [94] allegation that there should be a connection between risk and anxiety, however, this study confirmed this relation to both groups of respondents. This relation has been also proved from Saprikis & Avlogiaris' [73,78] studies in the broad context of m-commerce. According to our knowledge, this is the first empirical study where this relationship has been confirmed in the m-banking apps field.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Following Corbitt et al's [94] allegation that there should be a connection between risk and anxiety, however, this study confirmed this relation to both groups of respondents. This relation has been also proved from Saprikis & Avlogiaris' [73,78] studies in the broad context of m-commerce. According to our knowledge, this is the first empirical study where this relationship has been confirmed in the m-banking apps field.…”
Section: Discussionsupporting
confidence: 63%
“…Androulidakis & Androulidakis [84] mentioned that if users are subject to get rewarded when they conduct a transaction via a mobile device, they would be encouraged to use these services more frequently. Up to now, several studies have confirmed the positive effect of reward to the adoption of e-commerce (e.g., [78,82,85]). Hence, if banks enhance their m-banking app functionality with services such as financial incentives, they might have a greater chance of being adopted by their customers.…”
Section: Rewardmentioning
confidence: 89%
See 2 more Smart Citations
“…El eCommerce a través de RRSS o comercio social ya es una tendencia, se considera incluso una alternativa obvia e inevitable (Lv et al, 2020). El comercio social también ha mostrado ser un fenómeno que cada vez se utiliza más por los compradores, pueden hacer un comparativo de productos, concretar compras, atribuyéndole de igual forma que consideran que es una actividad cómoda y que tienen contacto directo con la empresa (Saprikis y Avlogiaris, 2021).…”
Section: Ecommerce En Las Redes Socialesunclassified